Elastic Properties of C-Type Lanthanide Sesquioxides - Yadav, Pooja; Yadav, Dheerendra Singh; Singh, Dharmvir; Singh, Pravesh; Verma, Ajay Singh (East European Journal of Physics, 2024)
In this study, we have presented the solid-state theory of plasma oscillations to investigate the anisotropic elastic properties such as three independent static elastic stiffness constants (Cij: C11, C12 & C44) of C-type Ln2O3 lanthanide solids. The calculated values of the static elastic stiffness constants of Ln2O3 are in excellent agreement with the theoretical results obtained by using ab-initio techniques. The values of elastic stiffness constants (Cij) exhibit a linear relationship when plotted against their plasma energies and lie on a straight line. To further examine the validity of the present estimations on elastic moduli and other parameters of these materials. The mechanical moduli such as bulk modulus (B), shear modulus (G), Young modulus (E), Poisson’s ratio (ν), shear wave constant (Cs), Cauchy pressure (C*), Lame’s coefficient (λ and µ), Kleinman parameter (ξ) Grunesien parameter (γ), Zener anisotropic constant (Z) and Pugh ratio (G/B) of lanthanide solids have also been investigated. For the lanthanide sesquioxide materials, the values of static elastic stiffness constants Cij and elastic moduli were presented for the first time. Unfortunately, in the current study, for many parameters of these materials, experimental results were not found for a comparison with our theoretical predictions. Our estimations agree well with the available experimental data and other theoretical reports.